The Utilization of Serratia marcescens to Increase Phosphate-Availability and Production of Cucumber in Alfisols - Abdillah, Muhammad Majid; Setiawati, Tri Candra (Jurnal ILMU DASAR, 2023)
Serratia marcescens is a bacterium that can dissolve phosphate (P) in soil, increasing phosphate availability and allowing plants to use it to support plant growth. P-available in the soil is generally low, including in Alfisols, due to the formation of bonds with Al, Fe, Ca, Mg, and other cations, which is influenced by soil pH or clay mineral adsorption. Cucumber plants require adequate nutrients, including P nutrients, for optimal growth and production. The study was carried out in a greenhouse using a completely randomized design (CRD) with four treatments and five replications. The treatments were S. marcescens bacterial solution concentrations of P0 (0 ml); P1 (20 ml); and P2 (20 ml); P3 (60 ml) bacterial colony density: 33x109 cfu/ml. According to the findings of the study, S. marcescens inoculation had a significant effect on increasing soil pH by 6,16, P-total concentration of 41,62 mg/100g, P-available concentration of 28,39 ppm, P-tissue concentration shoot and root were 0,30% and 0,78%, respectively, and P-root uptake of 2,27 g/pot. Similarly, S. marcescens inoculation significantly affected the plant height of 138,72 cm, root volume of 43 ml, and root length of 59,92 cm compared to the control treatment.